Digitally delivered contingency management during methadone treatment for people with co-occurring cocaine and opioid use: a protocol for a randomized controlled trial - Alexander, Karen; Sharma, Anjalee; Fletcher, Jesse B.; Smith, Zoe; Huddleston, Tori; Gryczynski, Jan; Stitzer, Maxine (Frontiers in Psychiatry, 2025)
BackgroundPeople in treatment for opioid use disorder (OUD) who also use cocaine are at heightened risk of early treatment discontinuation and poor outcomes. Digital therapeutics utilized within OUD treatment have the potential to impact public health by improving the evidence-based intervention delivery. Contingency management (CM) is an evidence-based intervention to reduce substance use, including cocaine. This article details a randomized controlled trial protocol that tests a digitally-delivered CM intervention for adult patients with co-occurring cocaine and opioid use entering methadone treatment.MethodsThis study will enroll 240 individuals within two weeks of beginning a new treatment episode at one of four participating opioid treatment programs (OTPs) in Baltimore, Maryland. Eligible adults must report past 30-day cocaine and opioid use at intake. Participants are randomized to receive either treatment as usual (TAU) or TAU plus the DynamiCare Contingency Management (DCM) app. The DCM app facilitates the provision of small monetary incentives for picking up methadone doses, completing cognitive behavioral therapy educational modules, and testing negative for cocaine or opioids on randomly-scheduled self-administered and validated oral fluid drug tests. The primary outcome is retention in methadone treatment. Participants are assessed at baseline, 3-, 6- and 12-months on measures including substance use and quality of life, and qualitative interviews are conducted with a subset of DCM-arm participants to assess acceptability and utility of the intervention. This trial was registered in the National Clinical Trials database on February 23, 2023, according to NIH policy (https://clinicaltrials.gov/study/NCT05766631).DiscussionThis project will inform the ancillary content of methadone maintenance treatment for the many patients with substance use disorders that extend beyond opioids, specifically for those who use cocaine. The study’s design will provide scientifically valid information about the effectiveness of digitally delivered CM, while app usage data and qualitative data from participants will be a rich resource for interpreting outcome results. CM is the only known evidence-based treatment for stimulant disorder, and digital delivery could solve many of the practical issues that have hampered widespread adoption of CM. Thus, the study could have both an important scientific and public health impact.